Physical activity and fracture risk: a prospective study of 1898 incident fractures among 34,696 British men and women. - Appleby, P; Allen, N; Roddam, A; Key, T (2008)
Regular physical activity is believed to have a beneficial effect on bone health but may also increase the risk of fractures by increasing the incidence of injury. We examined the association between physical activity and fracture risk in a prospective study of self-reported incident fractures among 34 696 men and women aged 20 to 89 years in the United Kingdom. Over an average of 5.2 years of follow-up, 343 men and 1555 women reported one or more fractures. For the 72% of fractures caused by a fall, the only significant association with physical activity was the lower fracture rate among women with a standing occupation compared with women in sedentary or no employment [incidence rate ratio, 0.81 (95% CI, 0.69-0.95)]. There was a strong positive association between bicycling and fracture risk: P < 0.001 for trend for both sexes. Regular participation in exercise and sports other than walking and bicycling was also associated with an increased fracture risk, and fracture rates were significantly higher for male manual workers compared with men in sedentary or no employment. These positive associations of physical activity with fracture risk applied primarily to fractures not caused by a fall. The relatively low fracture risk among women with a standing occupation might be the result of a beneficial effect of weight-bearing exercise. The markedly increased risk of fractures associated with bicycling, and the moderately increased risk associated with other exercise and sports, are probably the result of an increased incidence of injury.